2020
DOI: 10.1108/hff-04-2020-0223
|View full text |Cite
|
Sign up to set email alerts
|

Free convection and thermal radiation of nanofluid inside nonagon inclined cavity containing a porous medium influenced by magnetic field with variable direction in the presence of uniform heat generation/absorption

Abstract: Purpose The purpose of this paper is to study the natural convection and radiation heat transfer inside Nonagon inclined cavity with variable heated source length, which contains a porous medium saturated with nanofluid in the presence of uniform heat generation or absorption under the effect of uniform magnetic field with variable direction. The shape factor of nano particles is taking account for the model of nanofluid. Design/methodology/approach This study is established in two-dimensional space. The 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Also, Hatami et al 29 32 used the optimization techniques such as Response Surface Methodology (RSM) to find the optimize geometries including nanofluids in heat transfer applications. Massoudi et al 33 , 34 also investigated the nanofluids application in free convection under the influence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Hatami et al 29 32 used the optimization techniques such as Response Surface Methodology (RSM) to find the optimize geometries including nanofluids in heat transfer applications. Massoudi et al 33 , 34 also investigated the nanofluids application in free convection under the influence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies such as Teamah and El‐Maghlany 39 and Mliki et al 40 has been done to examine the effect of uniform heat generation or absorption on the heat transfer performance inside cavities, they pointed out that presence of uniform heat generation improves convective flow, however, the presence of uniform heat absorption reduces it. The effect of uniform convection heat flow and thermal radiation of a nanofluid under a magnetic field effect has been investigated in several studies 41‐43 . The results demonstrate that convective heat flow enhances in the presence of thermal radiation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ghalambaz et al 13 analyzed the heat transfer of nanoencapsulated phase change particle suspensions inside a coaxial pipe and found that a higher value of the nanoparticle's volume fraction enhances heat transfer. Massoudi et al 14 considered the flow of a nanofluid in a porous medium in the presence of uniform heat generation/absorption. Hamida et al 15 studied the impact of copper nanoparticles on a vertical plate.…”
Section: Introductionmentioning
confidence: 99%